Optimasi Parameter Produk 3D Printing Terhadap Kuat Tarik Menggunakan Filamen TPU (Thermoplastic Polyurethane) - Redy, Redy; Hasdiansah, Hasdiansah; Sirwansyah Suzen, Zaldy (Jurnal Inovasi Teknologi Terapan, 2023)
3D Printing is a change from printing technology which is being able to produce and design sophisticated structures in one unity. 3D printing is a process fabrication Fused Deposition Modeling (FDM) , that is Additive Manufacturing (AM) technology, which is a system that works by adding material layer by layer to form 3D objects. This research will use TPU (Thermoplastic polyurethane) filaments. Mechanically this TPU filament has good elastic mechanical properties. This research aims to obtain the highest tensile test value from the results of 3D printer printing with the specifications to be used, namely layer thickness, infill pattern, and Z-orientation. Printing will be carried out using the Anet A8 Plus machine and for the type of specimen using the ASTM D-638 type V standard. This study used taguchi L9 with 3 factors and 3 levels which printed 27 specimens. So that the highest score obtained in the tensile test with experiment number 7 was 12.97MPa and the lowest tensile test value was obtained in experiment number 2 with a value of 11.87MPa. For the results of the calculation of the S/N ratio, the most influential factor is the Z-orientation.